Do firm-level sustainability targets drive environmental innovation? Insights from BRICS Economies. (15th September 2021) - Ullah, Subhan; Nasim, Asma
Abstract: This paper examines the relationship between sustainability targets and their impacts on corporate environmental innovation. Using data over the period 2009-2018 on 202 companies from BRICS countries, covering firm-level governance, social responsibility and sustainability this paper examines firm-level sustainability targets, and incentives encourage managers to engage in more environmentally friendly activities. Using panel data probit regression, and after controlling for country-level governance and institutional factors, the study finds that embedding environmental targets in corporate strategy does encourage corporate managers to design and develop eco-friendly products and services, and such firm-level commitments at the top motivates managers to promote, market, and label environmentally friendly products. The findings call for greater emphasis on aligning executive compensation with sustainability targets rather than focusing too much on short-term accounting and market-based measures of firm performance. Highlights: We explore how sustainability related target impacts on corporate environmental innovation. 202 companies' data is collected for BRICS countries between 2009 and 2018. Panel data Probit estimation was employed to assess likelihood of environmental innovation. Environmental targets in corporate strategy does encourage corporate managers in developing eco-friendly products. More companies should be encouraged to include environmental targets in executive compensation.